A prospective observational study of demographic profile and maternal and neonatal outcomes in emergency obstetrics - Radhika; B. Jaju, Purshottam; Sondhi , Hitanshu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Emergency obstetric care (EmOC) is vital in reducing maternal and neonatal morbidity and mortality. Tertiary care centers serve as critical hubs for managing high-risk pregnancies and obstetric complications. Objectives were to evaluate the clinical profile, maternal morbidity, and neonatal outcomes of obstetric ICU admissions at a tertiary care center and assess associations with booking status and ICU stay duration. Methods: A prospective observational study was conducted at Al-Ameen Medical College Hospital, Karnataka, from July 2023 to January 2025. A total of 160 obstetric ICU patients meeting inclusion criteria were enrolled. Data on age, booking status, ICU diagnosis, length of stay, delivery mode, maternal morbidity, and NICU admissions were collected and analyzed using SPSS v23. Statistical significance was set at p<0.05. Results: Most patients were aged 31-40 years (43.8%) and unbooked (75%). Preeclampsia (25%), severe anemia (13.8%), and sepsis (12.5%) were the leading ICU admission causes. Maternal morbidity was significantly higher in unbooked patients (p=0.03). NICU admissions (27.5%) were significantly associated with ICU stay >7 days (p=0.001). Conclusions: Unbooked status and preventable complications are major contributors to ICU admissions. Strengthening antenatal services and improving referral systems are essential for better maternal and neonatal outcomes.